Identification of biorelevant dissolution media to assess biopharmaceutical performance of erlotinib formulation with enhanced bioavailability using physiologybased pharmacokinetic modeling (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The aim of the present work was to predict the bioavailability (BA) of poorly soluble drug. In vitro dissolutionof selected BCS Class II drug was conducted in different dissolution media to identify the discriminatory behaviorsof the dissolution media. Further, the development of physiology-based pharmacokinetic modeling performedusing GastroPlus® for BA predictions of formulation showing enhanced dissolution. Study Design: UsingGastroPlus® software (Simulations Plus, Lancaster, CA), a physiology-based pharmacokinetic model forerlotinib was developed. Erlotinib absorption was described using the advanced compartmental absorptionand transit model. The input parameters for the simulation were either determined experimentally or gatheredfrom the literature. Place and Duration of Study: Amity Institute of Pharmacy, Noida. Methodology: In vitrodissolution studies were conducted and data were analyze to find the biorelevent dissolution media. GastroPlus®model was built to predict the Cmax and AUC and also was validated for the prediction error